Development of a novel Ga-containing hydroxyapatite/chlorhexidine biomaterial with antibacterial properties for future application in bone tissue engineering: an experimental and theoretical study - Ewerton Gomes Vieira; Ricardo Barbosa Sousa; Marcos Pereira da Silva; Régis Casimiro Leal; Anderson Gomes Vieira; Wiury Chaves de Abreu; André L. Menezes de Oliveira; Maria Gardênnia da Fonseca; Santiago Medina Carrasco; Josy Anteveli Osajima; Edson C. Silva-Filho (Cerâmica)
Abstract This study focuses on synthesizing gallium-containing hydroxyapatite (Ga-HA) with chlorhexidine (CLX) for potential use in bone and dental tissue restoration. The Ga-HA/CLX materials were prepared using a suspension-precipitation method and were surface-functionalized with varying CLX concentrations. X-ray diffraction analysis confirmed the hexagonal structure of Ga-HA with space group P63/m, while XPS revealed the presence of gallium and a Ca/P ratio ranging from 1.50 to 1.72. Infrared spectra exhibited characteristic bands for phosphate and CH2 groups, indicating CLX incorporation. The Ga-HA/CLX materials demonstrated 100% inhibitory efficiency against Staphylococcus aureus and Escherichia coli bacterial strains. MTT assay indicated enhanced cell viability in the presence of gallium, with the Ga-HA/CLX-0.20 material classified as non-toxic with 81.0 ± 3% cell proliferation. Density Functional Theory calculations supported favorable thermodynamics in the interaction between hydroxyapatite and chlorhexidine. Overall, Ga-HA/CLX materials exhibit promising properties for biomedical applications.